2021
DOI: 10.46497/archrheumatol.2022.8669
|View full text |Cite
|
Sign up to set email alerts
|

Biological treatment in resistant adult-onset Still’s disease: A single-center, retrospective cohort study

Abstract: Objectives: The aim of this study was to assess the demographic and clinical characteristics of patients with adult-onset Still’s disease (AOSD) under biological treatment. Patients and methods: This retrospective cohort study included a total of 19 AOSD patients (13 males, 6 females; median age: 37 years; range, 28 to 52 years) who received biological drugs due to refractory disease between January 2008 and January 2020. The data of the patients were obtained from the patient files. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…42 The 44 studies were conducted across a range of countries across Europe and Asia, and in the USA. 4,26,27,33, Seventeen 26,33,43,44,46,47,49,52,57,59,62,63,66,69,[71][72][73] of the 44 studies reported that included patients had to be refractory to conventional treatment including CS and csDMARDs. In other studies, patients had undergone previous treatment, but failure on all conventional management was not an inclusion criterion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…42 The 44 studies were conducted across a range of countries across Europe and Asia, and in the USA. 4,26,27,33, Seventeen 26,33,43,44,46,47,49,52,57,59,62,63,66,69,[71][72][73] of the 44 studies reported that included patients had to be refractory to conventional treatment including CS and csDMARDs. In other studies, patients had undergone previous treatment, but failure on all conventional management was not an inclusion criterion.…”
Section: Resultsmentioning
confidence: 99%
“…For the case series, 23 were judged to be at a low ROB 4,42-46,48-50,52,53,55-57,59,61-63,65,66,68-70 and 17 at a high ROB. 26,27,47,51,54,67,[71][72][73][74][75][76][77][78][79][80][81] Reporting was often not clear or complete. Ten of the case series showed high ROB in 1 or 2 fields, most commonly relating to poor or nonexistent reporting of patient baseline characteristics or outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations